2020
DOI: 10.7717/peerj.8296
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variability of terrestrial diatoms at the catchment scale: controls on communities

Abstract: Diatoms are generally regarded as inhabitants of water bodies. However, numerous taxa are able to survive and reproduce in a variety of non-aquatic ecosystems. Although terrestrial diatoms are discussed extensively in the literature, most of those studies covered floristic aspects and few information exists on their ecology. This lack of knowledge thwarts their potential use as environmental markers in various applications. As a way forward, we investigated the seasonal patterns and the role of different distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…The performed statistical analysis showed a certain correlation between the numerous development of these species at the studied sites and the increase in the level of moisture. Foets et al (2020) indicated that diatoms have a number of features, including morphological ones that allow them to adapt to dynamic (daily, seasonal) changes in the environment, e.g. to the changes in moisture content.…”
Section: Discussionmentioning
confidence: 99%
“…The performed statistical analysis showed a certain correlation between the numerous development of these species at the studied sites and the increase in the level of moisture. Foets et al (2020) indicated that diatoms have a number of features, including morphological ones that allow them to adapt to dynamic (daily, seasonal) changes in the environment, e.g. to the changes in moisture content.…”
Section: Discussionmentioning
confidence: 99%
“…pH, moisture... see Lund, 1945;Van de Vijver et al, 2002) and anthropic disturbances (Antonelli et al, 2017;Foets et al, 2020). In a recent study Foets et al (2020), we showed that indicator species could be assigned to certain land use types (e.g. agricultural field, forest...), whereas in another study we indicated that the absolute abundances of soil diatom were related to available soil moisture content (Foets et al, in review).…”
Section: Introductionmentioning
confidence: 90%
“…Besides their high abundances in aquatic environments, they are also present in most terrestrial habitats where their diversified species distributions are mainly controlled by physiographical factors (e.g. pH, moisture... see Lund, 1945;Van de Vijver et al, 2002) and anthropic disturbances (Antonelli et al, 2017;Foets et al, 2020). In a recent study Foets et al (2020), we showed that indicator species could be assigned to certain land use types (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…Previously, we have investigated the temporal and spatial variability in the composition of soil diatom communities (Foets et al, 2020). There, we found that forests create a stable microhabitat for diatoms, that the temporal variation of the communities is mainly controlled by farming practices, and that they need one to two months to reestablish a new, stable community after a significant change in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed natural unit in which environmental variables such as radiation, temperature and soil moisture show the largest variability. The aim of this study is mainly exploratory, but while analyzing the data for Foets et al (2020), we also developed two hypotheses. Our first hypothesis states that soil diatom productivity (i.e.…”
Section: Introductionmentioning
confidence: 99%